PERKEMBANGAN OMNICHANNEL BRAND FESYEN DI INDONESIA - Susi Hartanto (Jurnal Da Moda, 2023)
Current fashion customers have been shopping through various channels, thus requiring strategies and integration between channels, both online and offline. Several brands, including Uniqlo, H&M, Pomelo, Love Bonito, Blibli, and Bata, are highlighted as case studies in this article. The article was compiled using a qualitative descriptive analysis method based on personal studies of various journals and leading fashion retailers or brands that offer omnichannel services in Indonesia. The hope is that this article can provide insights into the omnichannel strategies of leading fashion brands, so that adaptations or innovations can be considered by other fashion brands. Key words : fashion, omnichannel, brand, Indonesia